An Optimized Bacteriophage Cocktail Can Effectively Control Salmonella in vitro and in Galleria mellonella - Nale, Janet Y.; Vinner, Gurinder K.; Lopez, Viviana C.; Thanki, Anisha M.; Phothaworn, Preeda; Thiennimitr, Parameth; Garcia, Angela; AbuOun, Manal; Anjum, Muna F.; Korbsrisate, Sunee; Galyov, Edouard E.; Malik, Danish J.; et al. (Frontiers in Microbiology, 2021)
Salmonella spp. is a leading cause of gastrointestinal enteritis in humans where it is largely contracted via contaminated poultry and pork. Phages can be used to control Salmonella infection in the animals, which could break the cycle of infection before the products are accessible for consumption. Here, the potential of twenty-one myoviruses and a siphovirus to eliminate Salmonella in vitro and in vivo was examined with the aim of developing a biocontrol strategy to curtail the infection in poultry and swine. Together, the phages targeted the twenty-three poultry and ten swine prevalent Salmonella serotype isolates tested. Although individual phages significantly reduced bacterial growth of representative isolates within 6h post-infection, bacterial regrowth occurred 1h later, indicating proliferation of resistant strains. To curtail bacteriophage resistance, a novel three-phage cocktail was developed in vitro, and further investigated in an optimised Galleria mellonella larva Salmonella infection model colonised with representative pig, chicken and laboratory strains. For all the strains examined, G. mellonella larvae given phages 2 hours prior to bacterial exposure (prophylactic regimen) survived and Salmonella was undetectable 24h post-phage treatment and throughout the experimental time (72h). Administering phages with bacteria, or 2 hours post-bacterial exposure (remedial regimen) also improved survival (73-100% and 15-88%, respectively), but was less effective that prophylaxis application. These pre-livestock data support the future application of this cocktail to be developed further to effectively treat Salmonella infection in poultry and pigs. Future work will focus on cocktail formulation to ensure stability and incorporation into feeds and used to treat the infection in target animals.